Bundle-of-care interventions to improve self-management of patients with urinary catheters: Study protocol. Issue 3 (June 2022) - Alex, Joby; Ferguson, Caleb; Ramjan, Lucie M.; Montayre, Jed; Lombardo, Lien; Salamonson, Yenna
Abstract : Background: Community-based urinary catheter-associated complications contribute to avoidable, costly hospital presentations. To minimise catheter-associated complications and improve the quality of life of patients living in the community, it is essential to improve catheter self-management through increasing patients' and caregivers' knowledge and self-efficacy. Aim: To co-design, develop and evaluate a bundle-of-care intervention to improve catheter self-management, reduce catheter-associated complications, and improved quality of life. Design: Mixed methods design underpinned by the principles of Appreciative Inquiry, micro- and spaced-learning pedagogies. Methods: A co-designed care bundle will be developed, to support both patients and nurses in improving catheter care in both acute and community settings. Intervention bundles for patients will be delivered using "GoShare Healthcare" and for nurses, using QStream. The underpinning pedagogical approaches of these two digital platforms focus on increasing knowledge retention and improving patient health outcomes. A process evaluation of the intervention will be undertaken using data collected from surveys, electronic medical record audits, and participant interviews. The primary outcome is improved catheter self-management, and secondary outcomes are increased self-efficacy and patients' knowledge of catheter self-management. Discussion: The IQ-IDC study applies a two-pronged approach to co-design a bundle-of-care intervention that addresses important gaps in current catheter management. This study will contribute to new knowledge on effective implementation strategies to optimise self-management in urinary catheter care.